2011
DOI: 10.1242/jcs.092585
|View full text |Cite
|
Sign up to set email alerts
|

The epigenetic H3S10 phosphorylation mark is required for counteracting heterochromatic spreading and gene silencing inDrosophila melanogaster

Abstract: SummaryThe JIL-1 kinase localizes specifically to euchromatin interband regions of polytene chromosomes and is the kinase responsible for histone H3S10 phosphorylation at interphase. Genetic interaction assays with strong JIL-1 hypomorphic loss-of-function alleles have demonstrated that the JIL-1 protein can counterbalance the effect of the major heterochromatin components on position-effect variegation (PEV) and gene silencing. However, it is unclear whether this was a causative effect of the epigenetic H3S10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(59 citation statements)
references
References 35 publications
5
54
0
Order By: Relevance
“…At pericentric sites loss-of-function alleles of JIL-1 act as enhancers of PEV whereas gain-of-function alleles act as suppressors. 7 As predicted by the model, the results of Wang et al 5 showed that the level of the H3K9me2 mark at the reporter was inversely proportional to the H3S10ph level. PEV was enhanced with increased levels of H3K9me2 in the absence of H3S10 phosphorylation and PEV was suppressed with increased levels of the H3S10ph mark and a concomitant decrease in the level of the H3K9me2 mark.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…At pericentric sites loss-of-function alleles of JIL-1 act as enhancers of PEV whereas gain-of-function alleles act as suppressors. 7 As predicted by the model, the results of Wang et al 5 showed that the level of the H3K9me2 mark at the reporter was inversely proportional to the H3S10ph level. PEV was enhanced with increased levels of H3K9me2 in the absence of H3S10 phosphorylation and PEV was suppressed with increased levels of the H3S10ph mark and a concomitant decrease in the level of the H3K9me2 mark.…”
Section: Introductionmentioning
confidence: 73%
“…[1][2][3] These observations suggested a model for a dynamic balance between euchromatin and heterochromatin, 1,[3][4][5] where the level of gene expression is determined by antagonistic functions of the euchromatic H3S10ph mark and the heterochromatic H3K9me2 mark. 3,[5][6][7][8] Wang et al 5 tested this model by transgenically expressing various truncated versions of JIL-1, with or without kinase activity and correlating their effect on PEV with the levels of the H3S10ph and H3K9me2 marks at a hsp70-white reporter gene as determined by ChIP assays in the pericentric insertion line 118E-10. At pericentric sites loss-of-function alleles of JIL-1 act as enhancers of PEV whereas gain-of-function alleles act as suppressors.…”
Section: Introductionmentioning
confidence: 99%
“…that showed association of H3K9me2 spreading with decreased gene expression (27)(28)(29)(30). To examine this on a genome-wide scale, we stratified all of the genes into those in H3K9me2-spreading domains (3,930) and genes that are not in H3K9me2 in either control or Ni-exposed cells (8,096) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Ni-induced spreading of H3K9me2 is reminiscent of the local discrete changes, suggesting that misregulation of this regulatory switch results in altered gene expression. Furthermore, several earlier studies have suggested ectopic spreading of H3K9me2 to be an important signal for transcriptional silencing (27)(28)(29)(30)39). However, the alternate possibility of gene silencing resulting in spreading of H3K9me2 in a subset of the spreading domains cannot be ruled out.…”
Section: Discussionmentioning
confidence: 95%
“…The JIL-1 kinase and the H3S10 histone modification counteract heterochromatin spreading. [4][5][6][7][8][9][10] According to the current model of heterochromatin formation, Su(var)3-9 HKMT methylates the lysine 9 residue of histone H3. HP1a binds to H3K9me and then recruits another molecule of Su(var)3-9 for further methylation of H3 in the adjacent nucleosome.…”
Section: Introductionmentioning
confidence: 99%